Challenges of teleworking during the Covid-19 pandemic - Mile Vasic (Anali Ekonomskog fakulteta u Subotici, 2020)
The purpose of this paper is to determine how companies in the South-East European countries responded to the crisis caused by COVID-19 pandemic and work from home challenges, and what could be done in the future to overcome obstacles of working remotely. Forced by the pandemic to change the working style, companies needed to find the best possible solutions to ensure a sufficient level of working activities. Since such a challenge was faced for the first time in modern human history, not many companies were prepared for it. A quantitative approach was taken, using an online survey for the research. The findings are discussed and presented with reference to the relevant theories. The study reveals and points out the main concerns and problems related to working separately from the rest of the organization. The study analyzes how certain factors of working remotely such as lack of traditional leadership, physical workspace, isolation, etc. affected the life and work of employees during the crisis. The study is novel as these were the circumstances we had not faced before. The paper contributes to a better understanding of all of the aspects of teleworking, with an emphasis on social isolation and working under lockdown.